Circular economy in the restaurant sector: do practices go hand in hand? - Melo, António (2025)
The growing importance of sustainability has led the restaurant sector to explore circular economy practices to reduce waste and improve resource efficiency. This ongoing study examines the correlation between the adoption of one circular economy practice and the implementation of another within the restaurant sector. The study aims to identify specific practices that are related and assess the extent of these associations. A quantitative methodology was used with a survey that evaluated the adoption of 22 circular economy practices. Data collection was conducted between June and September 2023, resulting in 304 responses. Data were analyzed using SPSS version 28.0 with factor analysis employed to identify patterns of practice adoption. The results reveal that while some practices are indeed implemented together, such as energy-efficient equipment being strongly associated with monitoring energy consumption, many other practices did not exhibit significant correlations. For instance, waste reduction initiatives and water-saving measures often appeared isolated, without a consistent implementation linked to other practices. This suggests that restaurants may focus on aspects of circularity while neglecting others, indicating a fragmented rather than integrated approach. The findings point to key areas, such as waste management and energy efficiency, where more strategic interventions could encourage a holistic adoption of circular economy principles. These patterns underscore the need for further investigation into barriers that prevent cohesive practice implementation and opportunities for aligning efforts across multiple sustainability dimensions.